Recent food alerts and analytical advances related to the contamination of tropane and pyrrolizidine alkaloids in food - Casado, Natalia; Gañán, Judith; Morante-Zarcero, Sonia; Sierra, Isabel (Frontiers in Chemical Biology, 2024)
The food control of tropane and pyrrolizidine alkaloids has become in recent years in Europe one of the main priorities within the food safety field due to the exponential increase in food alerts related to the concerning levels of these natural toxins in foods. This awareness has led to increasing progress in the research and determination of these compounds. Hence, this mini-review provides a brief and comprehensive overview of the evolution of these food alerts, highlighting the main food products frequently contaminated with these alkaloids and reviewing the analytical advances in their determination within the las 3 years (from 2020 to 2023).